Polymeric Schiff base metal compound as well as preparation method and application thereof

By using polymerized Schiff alkali metal compounds as catalysts, combined with the synergistic coordination of long-chain polyether glycol and polymetal centers, the problems of low catalyst activity and complex preparation process in the prior art are solved, and efficient and environmentally friendly polypolytics are achieved Preparation of glycolic acid.

CN119119400AActive Publication Date: 2024-12-13CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411283404.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

During the preparation of existing polyglycolic acid, the catalyst has a low catalytic activity, and the preparation process is complex, the environmental pollution is serious, the yield is low, and the catalyst has poor solubility and high melting point, which affects the catalytic activity.

Method used

The polymerized Schiff alkali metal compound is used as a catalyst to improve solubility and dispersion by introducing long-chain polyether glycol, and catalytic activity is improved through multi-step reaction synthesis method, and the polymetal center synergistic coordination is used to improve catalytic activity.

Benefits of technology

High catalytic activity, high reaction yield, high product purity, reduced production costs and environmental pollution, the catalyst has good dispersion in glycolide, and the reaction rate has been increased to 97.2%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042364140000021
    Figure BDA0005042364140000021
  • Figure BDA0005042364140000051
    Figure BDA0005042364140000051
  • Figure BDA0005042364140000061
    Figure BDA0005042364140000061
Patent Text Reader

Abstract

The invention relates to the technical field of organic synthesis, in particular to a polymeric Schiff base metal compound and a preparation method and application thereof, and the polymeric Schiff base metal compound has a structure as shown in a formula I to a formula IV. The multi-center polymerization type Schiff base metal compound provided by the invention is simple in synthesis method, easy to purify and relatively high in product purity, and long-chain polyether glycol is introduced, so that the Schiff base catalyst is relatively low in melting point and relatively good in dispersion in glycolide; the polymeric Schiff base catalyst has a multi-center structure, and the catalytic activity of an original single-center catalyst can be improved through the synergistic coordination effect among multiple metal centers. The polymeric Schiff base catalyst provided by the invention has relatively high catalytic activity and has relatively high polymerization reaction speed when being used for catalyzing ring opening polymerization of glycolide to generate polyglycolic acid, and experimental results show that the reaction yield can reach 97.2% when the polymeric Schiff base catalyst is used for preparing the polyglycolic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic synthesis, and in particular to a polymeric Schiff base metal compound and a preparation method and application thereof. Background Art

[0002] Polyglycolic acid is a synthetic polymer material with good biodegradability and biocompatibility. It has excellent processing performance, mechanical strength and modulus, as well as high solvent resistance and high gas barrier properties. It can be used in medical polymer materials (such as surgical sutures and artificial skin, etc.). Polyglycolic acid can be decomposed into compounds that are friendly to the natural environment under the action of water, microorganisms and enzymes, so it has important application prospects as a biodegradable plastic in the fields of packaging materials and degradable films.

[0003] At present, the preparation of polyglycolic acid generally adopts cyclic ester ring-opening polymerization, such as glycolide ring-opening polymerization. In the process of cyclic ester ring-opening polymerization, stannous octoate is generally used as a catalyst for ring-opening polymerization, and its catalytic activity is much higher than that of other metal catalysts. In the commercial production of aliphatic polyesters, increasing the polymerization rate helps to improve production efficiency and reduce production costs. Among them, increasing the polymerization temperature is a solution to increase the polymerization rate. However, increasing the polymerization temperature will destroy the reaction balance, increase the depolymerization rate of the product, and seriously affect the molecular chain growth of the polymer. It will also increase side reactions, resulting in an increase in the yellowness index of the product. Another solution to increase the polymerization rate is to increase the amount of metal catalyst. In the ring-opening polymerization process of cyclic esters, if an excessive amount of metal catalyst is added to the reaction system, the residual metal compound in the product will reduce the thermal stability of the product.

[0004] Therefore, it is necessary to find a catalyst with higher activity to synthesize cyclic ester polymers. In recent years, Schiff base catalysts have been widely used due to their high catalytic activity. However, in its synthesis process, multi-step reactions are often required, and a large amount of solvent purification is required in each step. The preparation process is cumbersome, the environmental pollution is serious, and the yield is low. In addition, the current Schiff base catalysts have poor solubility and high melting point, and are not easy to disperse in the monomer, resulting in the catalytic activity of the catalyst being affected. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a polymeric Schiff base metal compound and a preparation method and application thereof, wherein the Schiff base metal compound has high catalytic activity.

[0006] To achieve the above object, the present invention provides a polymeric Schiff alkali metal compound having any structure of Formula I to Formula IV:

[0007]

[0008] wherein R1 is selected from substituted or unsubstituted alkyl, cycloalkyl, aryl or heteroaryl;

[0009] R2 is selected from the group remaining after removing two hydroxyl groups from polyether diol;

[0010] R3 is selected from hydrogen, halogen, nitro, substituted or unsubstituted alkyl or alkoxy;

[0011] R4 is selected from halogen, substituted or unsubstituted alkoxy or ester;

[0012] M1 is selected from zinc, cobalt, nickel or tin;

[0013] M2 is selected from aluminum, indium, chromium, iron, manganese, cerium or yttrium;

[0014] n is the degree of polymerization.

[0015] The R1 is preferably a substituted or unsubstituted C2-C6 alkyl, C3-C12 cycloalkyl, C6-C12 aryl or C4-C11 heteroaryl; more preferably a substituted or unsubstituted C2-C6 alkyl, C5-C6 cycloalkyl, C6 aryl or C4-C5 heteroaryl. The aryl or heteroaryl is preferably a monocyclic aryl or heteroaryl. The heteroatoms of the heteroaryl include, but are not limited to, one or more of N, O, and S. The R1 is further preferably a substituted or unsubstituted C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl or phenyl.

[0016] The substituent of R1 is preferably one or more of halogen, nitro, hydroxyl, amino, cyano, C1-C6 alkyl, C1-C6 alkoxy, C1-C6 haloalkyl, C1-C6 haloalkoxy, and more preferably one or more of fluorine, chlorine, bromine, nitro, hydroxyl, amino, cyano, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, methoxy, ethoxy, propoxy, fluoromethyl, difluoromethyl, and trifluoromethyl.

[0017] In some specific embodiments of the present invention, R1 is selected from ethylenediamine, 1,3-propylenediamine, 1,2-propylenediamine, 2-methyl-1,3-propylenediamine, 2,2'-dimethylpropylenediamine, 1,4-butylenediamine, 1,2-cyclohexyldiamine, o-phenylenediamine, 3-nitro o-phenylenediamine, 4-nitro o-phenylenediamine, 3-bromo o-phenylenediamine, 4-bromo o-phenylenediamine, 4,5-dibromo o-phenylenediamine, 4-bromo-5-fluoro o-phenylenediamine, 4-bromo-5-methyl o-phenylenediamine, 4-chloro-5-bromo o-phenylenediamine, 3-methyl-5-bromo o-phenylenediamine, The group remaining after removing two amino groups from 4-methoxy-o-phenylenediamine, 4-chloro-5-fluoro-o-phenylenediamine, 4,5-dichloro-o-phenylenediamine, 4-chloro-o-phenylenediamine, 4-trifluoromethyl-o-phenylenediamine, 3-chloro-o-phenylenediamine, 3-chloro-5-trifluoromethyl-o-phenylenediamine, 4,5-difluoro-o-phenylenediamine, 4-fluoro-o-phenylenediamine, 3-fluoro-o-phenylenediamine, 3,4-difluoro-o-phenylenediamine, 3,5-difluoro-o-phenylenediamine, 4,5-dimethyl-o-phenylenediamine, 4-methyl-o-phenylenediamine, 3,5-dimethyl-o-phenylenediamine or 4-chloro-5-methyl-o-phenylenediamine.

[0018] The R2 is preferably a group remaining after two hydroxy groups are removed from a polyether glycol, more preferably a group remaining after two hydroxy groups are removed from polyethylene glycol or polypropylene glycol. In some specific embodiments of the present invention, the R2 is a group remaining after two hydroxy groups are removed from polyethylene glycol 600, polyethylene glycol 800, polyethylene glycol 1000, polyethylene glycol 1500, polyethylene glycol 2000, polyethylene glycol 3000, polypropylene glycol 600, polypropylene glycol 1000, polypropylene glycol 1500, polypropylene glycol 2000, polypropylene glycol 3000, polytetrahydrofuran 650, polytetrahydrofuran 850, polytetrahydrofuran 1000, polytetrahydrofuran 2000 or polytetrahydrofuran 2900.

[0019] The R3 is preferably hydrogen, halogen, nitro, substituted or unsubstituted C1-C6 alkyl or C1-C6 alkoxy; more preferably hydrogen, halogen, nitro, substituted or unsubstituted C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C1 alkoxy, C2 alkoxy, C3 alkoxy, C4 alkoxy, C5 alkoxy, C6 alkoxy; further preferably hydrogen, halogen, nitro, substituted or unsubstituted methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, methoxy, ethoxy, n-propoxy or isopropoxy.

[0020] The substituent of R3 is preferably one or more of halogen, nitro, hydroxyl, amino, cyano, C1-C6 alkyl, C1-C6 alkoxy, C1-C6 haloalkyl, C1-C6 haloalkoxy, and more preferably one or more of fluorine, chlorine, bromine, nitro, hydroxyl, amino, cyano, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, methoxy, ethoxy, propoxy, fluoromethyl, difluoromethyl, and trifluoromethyl.

[0021] In some specific embodiments of the present invention, R3 is selected from hydrogen, -CH3, -CH2CH3, -CH(CH3)2, -OCH(CH3)2, -C(CH3)3, -OCH3 or -OCH2CH3.

[0022] The R4 is preferably halogen, substituted or unsubstituted C1-C6 alkoxy or ester; more preferably fluorine, chlorine, bromine, substituted or unsubstituted methoxy, ethoxy, n-propoxy, isopropoxy, methyl ester or ethyl ester.

[0023] The substituent of R4 is preferably one or more of halogen, nitro, hydroxyl, amino, cyano, C1-C6 alkyl, C1-C6 alkoxy, C1-C6 haloalkyl, C1-C6 haloalkoxy, and more preferably one or more of fluorine, chlorine, bromine, nitro, hydroxyl, amino, cyano, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, methoxy, ethoxy, propoxy, fluoromethyl, difluoromethyl, and trifluoromethyl.

[0024] In some specific embodiments of the present invention, the R4 is selected from -OCH3, -OCH2CH3, -OCH(CH3)2, -Cl or -OOCCH3.

[0025] The n is the degree of polymerization, and is preferably any integer of 5 to 100.

[0026] The present invention introduces a long-chain polyether diol into the structure of the above-mentioned polymeric Schiff alkali metal compound, so that the polymeric Schiff alkali metal compound has higher solubility, lower melting point, and better dispersibility in glycolide. The Schiff alkali metal compound is used as a catalyst for preparing cyclic ester polymers, has higher catalytic activity and higher reaction yield.

[0027] The present invention provides a method for preparing the above-mentioned polymeric Schiff alkali metal compound, comprising the following steps:

[0028] a) reacting a polyether glycol with an alkali metal to obtain a polyether glycol alkali metal salt;

[0029] b) reacting a polyether glycol alkali metal salt with chloromethyl salicylaldehyde to obtain a polyether glycol disalicylicylaldehyde compound;

[0030] c) reacting a polyether diol disalicylic aldehyde compound with a diamino compound to obtain a Schiff base polymer;

[0031] d) reacting the Schiff base polymer with a metal compound to obtain a polymeric Schiff base metal compound.

[0032] The polyether diol in the above step a) is preferably at least one of polyethylene glycol 600, polyethylene glycol 800, polyethylene glycol 1000, polyethylene glycol 1500, polyethylene glycol 2000, polyethylene glycol 3000, polypropylene glycol 600, polypropylene glycol 1000, polypropylene glycol 1500, polypropylene glycol 2000, polypropylene glycol 3000, polytetrahydrofuran 650, polytetrahydrofuran 850, polytetrahydrofuran 1000, polytetrahydrofuran 2000, and polytetrahydrofuran 2900.

[0033] The reaction temperature of the polyether diol and the alkali metal is preferably 25-100° C., and the reaction time is preferably 1-10 hours. The molar ratio of the polyether diol and the alkali metal is preferably 1:2.1-1:4. The alkali metal preferably includes one of lithium, sodium and potassium.

[0034] The present invention has no particular limitation on the source of the chloromethyl salicylaldehyde, which can be commercially available or prepared according to methods well known to those skilled in the art. Preferably, the synthesis of the chloromethyl salicylaldehyde comprises the following steps:

[0035] The salicylaldehyde compounds and formaldehyde compounds are reacted with a catalyst to generate chloromethyl salicylaldehyde.

[0036] The salicylaldehyde compound preferably includes at least one of salicylaldehyde, 3-methyl salicylaldehyde, 3-methoxy salicylaldehyde, 3-ethoxy salicylaldehyde, 3-tert-butyl salicylaldehyde, 3-bromo salicylaldehyde, 3-chloro salicylaldehyde, 5-chloro salicylaldehyde, 5-methyl salicylaldehyde, and 5-nitrosalicylicylaldehyde.

[0037] The formaldehyde compound preferably includes at least one of formaldehyde, trioxymethylene or polyoxymethylene.

[0038] The molar ratio of the salicylaldehyde compound to the formaldehyde compound is preferably 1:1 to 1:2.

[0039] The reaction temperature is preferably 0 to 95° C., and the reaction time is preferably 2 to 60 h.

[0040] The catalyst is preferably at least one of HCl, concentrated sulfuric acid, phosphoric acid, acetic acid, aluminum chloride, zinc chloride, and tin chloride.

[0041] In the step b), the molar ratio of the chloromethyl salicylaldehyde to the polyether glycol alkali metal salt is preferably 2:1 to 3:1, the reaction temperature is preferably 20 to 120° C., and the reaction time is preferably 2 to 48 hours.

[0042] In some specific embodiments of the present invention, the reaction equation of step b) is as follows:

[0043]

[0044]

[0045] Wherein, M is selected from lithium, sodium or potassium.

[0046] In the step c), the molar ratio of the polyether diol disalicylic aldehyde compound to the diamino compound is preferably 1:0.6-1.5, the reaction temperature is preferably 20-100° C., and the reaction time is preferably 2-48 hours.

[0047] The diamino compounds preferably include ethylenediamine, 1,3-propylenediamine, 1,2-propylenediamine, 2-methyl-1,3-propylenediamine, 2,2'-dimethylpropylenediamine, 1,4-butylenediamine, 1,2-cyclohexyldiamine, o-phenylenediamine, 3-nitro o-phenylenediamine, 4-nitro o-phenylenediamine, 3-bromo o-phenylenediamine, 4-bromo o-phenylenediamine, 4,5-dibromo o-phenylenediamine, 4-bromo-5-fluoro o-phenylenediamine, 4-bromo-5-methyl o-phenylenediamine, 4-chloro-5-bromo o-phenylenediamine, 3-methyl-5-bromo o-phenylenediamine, 4- At least one of methoxy o-phenylenediamine, 4-chloro-5-fluoro o-phenylenediamine, 4,5-dichloro o-phenylenediamine, 4-chloro o-phenylenediamine, 4-trifluoromethyl o-phenylenediamine, 3-chloro-o-phenylenediamine, 3-chloro-5-trifluoromethyl o-phenylenediamine, 4,5-difluoro o-phenylenediamine, 4-fluoro o-phenylenediamine, 3-fluoro o-phenylenediamine, 3,4-difluoro o-phenylenediamine, 3,5-difluoro o-phenylenediamine, 4,5-dimethyl o-phenylenediamine, 4-methyl-o-phenylenediamine, 3,5-dimethyl o-phenylenediamine, and 4-chloro-5-methyl o-phenylenediamine.

[0048] In some specific embodiments of the present invention, the reaction equation of step c) is as follows:

[0049]

[0050] In the step d), the metal compound preferably includes at least one of zinc chloride, zinc acetate, ethyl zinc, stannous chloride, ferric chloride, indium chloride, cobalt acetate, aluminum isopropoxide, aluminum ethoxide, nickel acetate and triethylaluminum.

[0051] Preferably, the molar ratio of the diamino compound residue in the Schiff base polymer to the metal compound is preferably 1:1 to 1:1.2, the reaction temperature is preferably 20 to 120° C., and the reaction time is preferably 2 to 100 h.

[0052] In some specific embodiments of the present invention, the reaction equations of step c) and step d) are as follows:

[0053]

[0054] The present invention provides the use of the polymeric Schiff alkali metal compound or the polymeric Schiff alkali metal compound prepared by the above preparation method as a catalyst in the preparation of cyclic ester polymers.

[0055] Preferably, the cyclic ester polymer is polyglycolic acid.

[0056] Based on this, the present invention provides a method for preparing polyglycolic acid, comprising the following steps:

[0057] In an inert atmosphere, glycolide or a mixture of glycolide and an epoxy compound is reacted in the presence of a catalyst and an initiator to obtain polyglycolic acid;

[0058] The catalyst is the above-mentioned polymeric Schiff alkali metal compound or the polymeric Schiff alkali metal compound prepared by the above-mentioned preparation method.

[0059] The initiator is preferably an alcohol substance.

[0060] The ratio of the mass of the catalyst to the mass of glycolide is preferably 1:(20-2000).

[0061] The molar ratio of the initiator to glycolide is preferably 1:(100-2000).

[0062] The ratio of the mole number of the epoxy compound to the mole number of the glycolide is preferably (0-10):(90-100).

[0063] The reaction temperature is preferably 120-240° C., and the reaction time is preferably 2-24 hours.

[0064] The epoxy compound is preferably any one or more of propylene oxide, butylene oxide, 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 1,2-epoxyoctane, 1,2-epoxydodecane, 1,2-epoxytetradecane, 1,2-epoxyhexadecane, allyl glycidyl ether, styrene oxide, isopropyl glycidyl ether, tert-butyl glycidyl ether, octyl glycidyl ether, phenyl glycidyl ether, 2-toluene glycidyl ether or benzyl glycidyl ether.

[0065] In the above reaction, the epoxy compound may be added or not, and whether it is added depends on the metal element in the catalyst. When the metal element is aluminum, tin or indium, the amount of epoxy compound added is 0; when the metal element is zinc, iron, cobalt, nickel, manganese, chromium, cerium or yttrium, the amount of epoxy compound added is not 0.

[0066] The preparation method has mild reaction conditions, high product yield and reduced production cost of the catalyst.

[0067] Compared with the prior art, the present invention provides a polymeric Schiff alkali metal compound having structures shown in Formulas I to IV.

[0068] The multi-center polymeric Schiff base metal compound synthesis method provided by the present invention is simple, easy to purify, and has a high product purity. Due to the introduction of long-chain polyether diol, the Schiff base catalyst has a low melting point and is better dispersed in glycolide; the polymeric Schiff base catalyst has a multi-center structure, and the catalytic activity of the original single-center catalyst can be improved through the synergistic coordination between the multi-metal centers. The polymeric Schiff base catalyst provided by the present invention has a high catalytic activity, and is used to catalyze the ring-opening polymerization of glycolide to generate polyglycolic acid, and has a high polymerization reaction speed. Experimental results show that the reaction yield of polyglycolic acid prepared by the catalyst of the present invention can reach 97.2%. DETAILED DESCRIPTION

[0069] In order to further illustrate the present invention, the polymeric Schiff alkali metal compound provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0070] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0071] Example 1

[0072] 0.1 mol of polyethylene glycol 600, 0.3 mol of metallic sodium and 200 mL of anhydrous toluene were added into a 1 L round-bottom flask, mixed and stirred and heated to 65° C. After the metallic sodium no longer decreased, the unreacted metallic sodium was removed, and then the toluene was removed in vacuo to obtain sodium polyethylene glycol.

[0073] The sodium polyethylene glycol (polyethylene glycol 800), sodium polyethylene glycol (polyethylene glycol 1000), and sodium polypropylene glycol (polypropylene glycol 1000) used in the following examples of the present invention are all prepared according to the above method, except that polyethylene glycol 600 is replaced by polyethylene glycol 800, polyethylene glycol 1000, and polypropylene glycol 1000.

[0074] Example 2

[0075] 2.1 Add 178g 3-tert-butyl salicylaldehyde, 97.3g formaldehyde solution (37wt%) and 1000mL concentrated hydrochloric acid (37wt%) to a 2L round-bottom flask, mix and stir, and continuously pass concentrated sulfuric acid dried HCl gas, the reaction temperature is 10°C, pass HCl gas for 12h, then seal the round-bottom flask, stir at 30°C for 36h, then heat to 70°C and stir for 36h, cool to 25°C, dissolve the crude product with ether and transfer to a separatory funnel, stand to separate the aqueous solution, wash the ether solution with saturated sodium bicarbonate solution to neutrality, and then wash three times with saturated NaCl solution. Dry the ether solution with anhydrous magnesium sulfate for 24h, filter and remove the solvent under normal pressure, then recrystallize the resulting solid with petroleum ether, and vacuum dry at 35°C for 24h to obtain 5-chloromethyl-3-tert-butyl salicylaldehyde 209.1g, purity 99.5%.

[0076] 2.2 Dissolve 52.2 g of sodium polypropylene glycol (polypropylene glycol 1000) prepared in Example 1 in 300 mL of toluene, and then add it dropwise at a rate of 2 mL / min to a 300 mL toluene solution of 22.7 g of 5-chloromethyl-3-tert-butyl salicylaldehyde. After the addition is complete, raise the temperature to 70°C, react for 3 h, stop heating, add 100 mL of water, mix well, and transfer the material to a separatory funnel. Let it stand to separate the salt solution. Wash the oil phase with deionized water several times until the water phase is neutral, add 40 g of anhydrous sodium sulfate, dry for 24 h, filter and remove the solvent in vacuo to obtain 65.5 g of disalicylicylaldehyde compound.

[0077] The obtained disalicylicylaldehyde compound was analyzed by nuclear magnetic resonance, and the hydrogen spectrum results were as follows: δ=10.09-10.31ppm corresponds to the characteristic chemical shift of hydrogen on the aldehyde group in salicylaldehyde, δ=7.02-7.38ppm corresponds to the characteristic chemical shift of hydrogen on the benzene ring in salicylaldehyde, δ=4.75-4.86ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group connected to the benzene ring in salicylaldehyde, δ=3.29-3.41ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group adjacent to oxygen in polypropylene glycol, δ=1.71-1.82ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group not adjacent to oxygen in polypropylene glycol, and δ=1.33-1.46ppm corresponds to the characteristic chemical shift of hydrogen on the tert-butyl group in salicylaldehyde.

[0078] This proves the successful synthesis of disalicylicylaldehyde compounds.

[0079] Example 3

[0080] 3.1 Add 136g 3-methyl salicylaldehyde, 89.2g formaldehyde solution (37wt%) and 800mL concentrated hydrochloric acid (37wt%) to a 2L round-bottom flask, mix and stir, and continuously introduce HCl gas dried with concentrated sulfuric acid. The reaction temperature is 15°C, and the HCl gas is introduced for 10h. Then the round-bottom flask is sealed, stirred at 25°C for 30h, then heated to 60°C and stirred for 30h, cooled to 25°C, the crude product is dissolved with ether and transferred to a separatory funnel, and the aqueous solution is separated by standing. The ether solution is washed with saturated sodium bicarbonate solution until neutral, and then washed three times with saturated NaCl solution. The ether solution is dried with anhydrous magnesium sulfate for 24h, filtered, and the solvent is removed under normal pressure, and then the resulting solid is recrystallized with petroleum ether and vacuum dried at 30°C for 24h to obtain 170g 5-chloromethyl-3-methyl salicylaldehyde with a purity of 99.8%.

[0081] 3.2 32.2 g of sodium polyethylene glycol (polyethylene glycol 600) prepared in Example 1 was dissolved in 400 mL of toluene, and then added dropwise at a rate of 2 mL / min to a 250 mL toluene solution of 18.4 g of 5-chloromethyl-3-methyl salicylaldehyde. After the addition was complete, the temperature was raised to 65°C, the reaction was continued for 6 h, the heating was stopped, 150 mL of water was added, the mixture was mixed evenly, and the material was transferred to a separatory funnel. The mixture was allowed to stand to separate the deionized water solution. The oil phase was washed with deionized water several times until the water phase was neutral. 60 g of anhydrous sodium sulfate was added and dried for 24 h. After filtering, the solvent was removed in vacuo to obtain 42.5 g of a disalicylicylaldehyde compound.

[0082] The obtained disalicylicylaldehyde compound was analyzed by nuclear magnetic resonance, and the hydrogen spectrum results were obtained as follows: δ=10.11-10.29ppm corresponds to the characteristic chemical shift of hydrogen on the aldehyde group in salicylaldehyde, δ=7.03-7.41ppm corresponds to the characteristic chemical shift of hydrogen on the benzene ring in salicylaldehyde, δ=4.76-4.85ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group connected to the benzene ring in salicylaldehyde, δ=3.41-3.62ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group in polyethylene glycol, and δ=2.09-2.21ppm corresponds to the characteristic chemical shift of hydrogen on the methyl group in salicylaldehyde.

[0083] This proves the successful synthesis of disalicylicylaldehyde compounds.

[0084] Example 4

[0085] 4.1 Add 76g 3-methoxy salicylaldehyde, 48.6g formaldehyde solution (37wt%) and 600mL concentrated hydrochloric acid (37wt%) to a 2L round-bottom flask, mix and stir, and continuously introduce HCl gas dried with concentrated sulfuric acid. The reaction temperature is 5°C, and the HCl gas is introduced for 15h. Then the round-bottom flask is sealed, stirred at 35°C for 33h, then heated to 50°C and stirred for 24h, cooled to 25°C, the crude product is dissolved with ether and transferred to a separatory funnel, and the aqueous solution is separated by standing. The ether solution is washed with saturated sodium bicarbonate solution until neutral, and then washed three times with saturated NaCl solution. The ether solution is dried with anhydrous magnesium sulfate for 24h, filtered, and the solvent is removed under normal pressure, and then the resulting solid is recrystallized with petroleum ether and vacuum dried at 25°C for 24h to obtain 91.2g of 5-chloromethyl-3-methoxy salicylaldehyde with a purity of 99.6%.

[0086] 4.2 42.2 g of sodium polyethylene glycol (polyethylene glycol 800) prepared in Example 1 was dissolved in 500 mL of toluene, and then added dropwise at a rate of 3 mL / min to a 400 mL toluene solution of 20 g of 5-chloromethyl-3-methoxysalicylaldehyde. After the addition was complete, the temperature was raised to 60°C, the reaction was continued for 10 h, the heating was stopped, 200 mL of water was added to dissolve, the mixture was mixed evenly, and the mixture was transferred to a separatory funnel. The mixture was allowed to stand to separate the deionized water solution. The oil phase was washed with deionized water several times until the water phase was neutral, 80 g of anhydrous sodium sulfate was added, and the mixture was dried for 24 h. After filtering, the solvent was removed in vacuo to obtain 50.2 g of a disalicylicylaldehyde compound.

[0087] The obtained disalicylicylaldehyde compound was analyzed by nuclear magnetic resonance, and the hydrogen spectrum results were obtained as follows: δ=10.13-10.31ppm corresponds to the characteristic chemical shift of hydrogen on the aldehyde group in salicylaldehyde, δ=7.05-7.36ppm corresponds to the characteristic chemical shift of hydrogen on the benzene ring in salicylaldehyde, δ=4.76-4.88ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group connected to the benzene ring in salicylaldehyde, δ=3.75-3.91ppm corresponds to the characteristic chemical shift of hydrogen on the methoxy group in salicylaldehyde, and δ=3.45-3.65ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group in polyethylene glycol.

[0088] This proves the successful synthesis of disalicylicylaldehyde compounds.

[0089] Example 5

[0090] 5.1 Add 68g 5-methyl salicylaldehyde, 56.8g formaldehyde solution (37wt%) and 400mL concentrated hydrochloric acid (37wt%) to a 2L round-bottom flask, mix and stir, and continuously introduce HCl gas dried with concentrated sulfuric acid. The reaction temperature is 10°C, and the HCl gas is introduced for 10h. Then the round-bottom flask is sealed, stirred at 40°C for 24h, then heated to 70°C and stirred for 20h, cooled to 25°C, the crude product is dissolved with ether and transferred to a separatory funnel, and the aqueous solution is separated by standing. The ether solution is washed with saturated sodium bicarbonate solution until neutral, and then washed three times with saturated NaCl solution. The ether solution is dried with anhydrous magnesium sulfate for 24h, filtered and the solvent is removed under normal pressure, and then the resulting solid is recrystallized with petroleum ether and vacuum dried at 25°C for 24h to obtain 83.3g of 3-chloromethyl-5-methyl salicylaldehyde with a purity of 99.7%.

[0091] 5.2 Dissolve 52.2 g of sodium polyethylene glycol (polyethylene glycol 1000) prepared in Example 1 in 600 mL of toluene, and then add it dropwise at a rate of 3 mL / min to a 300 mL toluene solution of 18.4 g of 3-chloromethyl-5-methyl salicylaldehyde. After the addition is complete, raise the temperature to 70°C, react for 10 h, stop heating, add 250 mL of water, mix well, and transfer the material to a separatory funnel. Let it stand to separate the deionized water solution. Wash the oil phase with deionized water several times until the water phase is neutral, add 100 g of anhydrous sodium sulfate, dry for 24 h, filter, and remove the solvent in vacuo to obtain 62 g of disalicylicylaldehyde compound.

[0092] The obtained disalicylaldehyde compound was analyzed by nuclear magnetic resonance, and the hydrogen spectrum results were obtained as follows: δ=10.11-10.28ppm corresponds to the characteristic chemical shift of hydrogen on the aldehyde group in salicylaldehyde, δ=7.21-7.59ppm corresponds to the characteristic chemical shift of hydrogen on the benzene ring in salicylaldehyde, δ=4.76-4.88ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group connected to the benzene ring in salicylaldehyde, δ=3.45-3.65ppm corresponds to the characteristic chemical shift of hydrogen on the methylene group in polyethylene glycol, and δ=2.28-2.44ppm corresponds to the characteristic chemical shift of hydrogen on the methyl group in salicylaldehyde.

[0093] This proves the successful synthesis of disalicylicylaldehyde compounds.

[0094] Example 6

[0095] 6.1 30.4 g of the disalicylic aldehyde compound prepared in Example 2 was dissolved in 300 mL of toluene, mixed with 1.2 g of ethylenediamine, and heated to 65°C. After 10 h, the toluene was removed by vacuum at a vacuum degree of 300 Pa. When no more liquid was distilled out, 50 mL of ethanol was added for washing, filtered, and dried to obtain 28.9 g of a polymeric Schiff base.

[0096] The obtained polymeric Schiff base was subjected to gel permeation chromatography analysis, and the number average molecular weight of the polymeric Schiff base was measured to be 20100 g / mol.

[0097] 6.2 Dissolve 15 g of the polymeric Schiff base prepared in 6.1 above in 200 mL of toluene, mix with 1.1 g of triethylaluminum in 20 mL of toluene solution, heat to 80°C, add 10 mL of ethanol after 24 hours, and remove toluene and ethanol by vacuuming at a vacuum degree of 300 Pa after 3 hours. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 14.4 g of polymeric Schiff base aluminum catalyst.

[0098] 6.3 The reaction bottle was repeatedly evacuated and filled with nitrogen, and 116 g of glycolide, 0.1 g of benzyl alcohol and 1.6 g of the Schiff base aluminum catalyst prepared in 6.2 were added to the reaction bottle in sequence. The mixture was stirred and the temperature was rapidly raised to 180°C. After 7 hours, 112.7 g of polyglycolic acid was obtained with a yield of 97.2%.

[0099] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 96000 g / mol.

[0100] Example 7

[0101] 7.1 30.1 g of the disalicylic aldehyde compound prepared in Example 2 was dissolved in 300 mL of toluene, mixed with 1.5 g of 1,3-propylenediamine, and heated to 70°C. After 8 h, the toluene was removed by vacuum at a vacuum degree of 300 Pa. When no more liquid was distilled out, 100 mL of ethanol was added for washing, filtered, and dried to obtain 29 g of a polymeric Schiff base.

[0102] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 23300 g / mol.

[0103] 7.2 Dissolve 15 g of the polymeric Schiff base prepared in 7.1 above in 150 mL of tetrahydrofuran, mix with 30 mL of ethanol solution of 1.4 g of zinc chloride, heat to 60°C, and after 48 hours, remove the tetrahydrofuran and ethanol by vacuuming at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 14.1 g of a polymeric Schiff base zinc catalyst.

[0104] 7.3 The reaction flask was repeatedly evacuated and filled with nitrogen, and 232 g of glycolide, 0.2 g of benzyl alcohol, 2.6 g of tert-butyl glycidyl ether and 3 g of the Schiff base zinc catalyst prepared in 7.2 were added into the reaction flask in sequence. The mixture was mixed and stirred and the temperature was rapidly raised to 185°C. After 6 hours, 222.9 g of polyglycolic acid was obtained with a yield of 96.1%.

[0105] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 83000 g / mol.

[0106] Example 8

[0107] 8.1 Dissolve 29.8 g of the disalicylic aldehyde compound prepared in Example 2 in 200 mL of toluene, mix with 2.3 g of 1,2-cyclohexanediamine, stir and heat to 75°C. After 6 h, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 100 mL of ethanol for washing, filter and dry to obtain 29.5 g of polymeric Schiff base.

[0108] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 26900 g / mol.

[0109] 8.2 Dissolve 16 g of the polymeric Schiff base prepared in 8.1 above in 250 mL of toluene, mix with 30 mL of toluene solution of 2 g of aluminum isopropoxide, heat to 85°C, and after 30 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 15.9 g of a polymeric Schiff base aluminum catalyst.

[0110] 8.3 The reaction bottle was repeatedly evacuated and filled with nitrogen, and 116 g of glycolide, 0.1 g of benzyl alcohol and 1.7 g of the above-mentioned Schiff base aluminum catalyst were added into the reaction bottle in sequence. After mixing and stirring, the temperature was rapidly raised to 190°C. After 5 hours, 112.4 g of polyglycolic acid was obtained with a yield of 96.9%.

[0111] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 95000 g / mol.

[0112] Example 9

[0113] 9.1 Dissolve 19.2 g of the disalicylic aldehyde compound prepared in Example 3 in 250 mL of toluene, mix with 3.1 g of 4-nitro-o-phenylenediamine, stir and heat to 60°C. After 12 h, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 150 mL of ethanol for washing, filter and dry to obtain 20.2 g of polymeric Schiff base.

[0114] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 23000 g / mol.

[0115] 9.2 Dissolve 11 g of the polymeric Schiff base prepared in 9.1 above in 200 mL of tetrahydrofuran, mix with 1.8 g of cobalt acetate in 30 mL of ethanol solution, heat to 55°C, and after 60 h, remove the tetrahydrofuran and ethanol under vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 10.5 g of a polymeric Schiff base cobalt catalyst.

[0116] 9.3 The reaction flask was repeatedly evacuated and filled with nitrogen, and 232 g of glycolide, 0.22 g of benzyl alcohol, 3 g of phenyl glycidyl ether and 2.3 g of the Schiff base cobalt catalyst prepared in 9.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 195°C. After 4 hours, 223.4 g of polyglycolic acid was obtained with a yield of 96.3%.

[0117] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 88000 g / mol.

[0118] Example 10

[0119] 10.1 Dissolve 20 g of the disalicylic aldehyde compound prepared in Example 3 in 300 mL of tetrahydrofuran, mix with 3.74 g of 4-bromo-o-phenylenediamine, stir and heat to 55°C. After 15 h, remove the tetrahydrofuran by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 200 mL of ethanol for washing, filter and dry to obtain 21.5 g of polymeric Schiff base.

[0120] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 13000 g / mol.

[0121] 10.2 Dissolve 11.5 g of the polymeric Schiff base prepared in 10.1 above in 150 mL of toluene, mix with 20 mL of toluene solution of 1.62 g of ethoxyaluminum, heat to 80°C, and after 36 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol, wash, filter, and dry to obtain 11.4 g of a polymeric Schiff base aluminum catalyst.

[0122] 10.3 The reaction flask was repeatedly evacuated and filled with nitrogen, 232 g of glycolide, 0.2 g of benzyl alcohol and 2.4 g of the Schiff base aluminum catalyst prepared in 10.2 were added into the reaction flask in sequence, mixed and stirred, and the temperature was rapidly raised to 190°C. After 8 hours, 223.9 g of polyglycolic acid was obtained with a yield of 96.5%.

[0123] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 99000 g / mol.

[0124] Embodiment 11

[0125] 11.1 Dissolve 20.6 g of the disalicylic aldehyde compound prepared in Example 3 in 350 mL of toluene, mix with 2.16 g of o-phenylenediamine, stir and heat to 50°C. After 18 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 250 mL of ethanol for washing, filter and dry to obtain 20.5 g of polymeric Schiff base.

[0126] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 10000 g / mol.

[0127] 11.2 Dissolve 11 g of the polymeric Schiff base prepared in 11.1 above in 150 mL of tetrahydrofuran, mix with 1.83 g of zinc acetate in 40 mL of ethanol, heat to 65°C, and after 36 hours, remove the tetrahydrofuran and ethanol by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 10.6 g of a polymeric Schiff base zinc catalyst.

[0128] 11.3 The reaction flask was repeatedly evacuated and filled with nitrogen. 232 g of glycolide, 0.2 g of benzyl alcohol, 1.16 g of isopropyl glycidyl ether and 2.2 g of the Schiff base zinc catalyst prepared in 11.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 185°C. After 12 h, 220.6 g of polyglycolic acid was obtained with a yield of 95.1%.

[0129] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 85000 g / mol.

[0130] Example 12

[0131] 12.1 Dissolve 27.1 g of the disalicylicaldehyde compound prepared in Example 4 in 400 mL of toluene, mix with 2.83 g of 4-chloro-o-phenylenediamine, stir and heat to 55°C. After 10 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 200 mL of ethanol for washing, filter and dry to obtain 27 g of polymeric Schiff base.

[0132] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 10200 g / mol.

[0133] 12.2 Dissolve 14 g of the polymeric Schiff base prepared in 12.1 above in 200 mL of tetrahydrofuran, mix with 2.21 g of indium chloride in 30 mL of ethanol solution, heat to 50°C, and after 72 h, remove the tetrahydrofuran and ethanol under vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 14.1 g of a polymeric Schiff base indium catalyst.

[0134] 12.3 The reaction flask was repeatedly evacuated and filled with nitrogen. 116 g of glycolide, 0.1 g of benzyl alcohol and 1.6 g of the Schiff base indium catalyst prepared in 12.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 175°C. After 9 hours, 110.5 g of polyglycolic acid was obtained with a yield of 95.3%.

[0135] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 92000 g / mol.

[0136] Example 13

[0137] 13.1 Dissolve 25.94 g of the disalicylic aldehyde compound prepared in Example 4 in 450 mL of toluene, mix with 1.48 g of 1,2-propylenediamine, stir and heat to 60°C. After 8 h, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 150 mL of ethanol for washing, filter and dry to obtain 24.9 g of polymeric Schiff base.

[0138] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 13200 g / mol.

[0139] 13.2 Dissolve 13.5 g of the polymeric Schiff base prepared in 13.1 above in 250 mL of tetrahydrofuran, mix with 1.76 g of nickel acetate in 40 mL of ethanol solution, heat to 55°C, and after 84 hours, remove the tetrahydrofuran and ethanol by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 12.9 g of a polymeric Schiff base nickel catalyst.

[0140] 13.3 The reaction flask was repeatedly evacuated and filled with nitrogen. 232 g of glycolide, 0.25 g of benzyl alcohol, 1.5 g of phenyl glycidyl ether and 2.8 g of the Schiff base nickel catalyst prepared in 13.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 170°C. After 12 h, 221.8 g of polyglycolic acid was obtained with a yield of 95.6%.

[0141] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 78000 g / mol.

[0142] Embodiment 14

[0143] 14.1 Dissolve 25.3 g of the disalicylic aldehyde compound prepared in Example 4 in 400 mL of toluene, mix with 1.76 g of 2-methyl-1,3-propylenediamine, stir and heat to 55°C. After 20 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 100 mL of ethanol for washing, filter and dry to obtain 24.6 g of polymeric Schiff base.

[0144] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 15800 g / mol.

[0145] 14.2 Dissolve 13 g of the polymeric Schiff base prepared in 14.1 above in 200 mL of toluene, mix with 30 mL of toluene solution of 2.04 g of aluminum isopropoxide, heat to 85°C, and after 48 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol, wash, filter, and dry to obtain 13 g of a polymeric Schiff base aluminum catalyst.

[0146] 14.3 The reaction flask was repeatedly evacuated and filled with nitrogen. 232 g of glycolide, 0.2 g of benzyl alcohol and 2.8 g of the Schiff base aluminum catalyst prepared in 14.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 165°C. After 15 h, 224.1 g of polyglycolic acid was obtained with a yield of 96.6%.

[0147] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 91000 g / mol.

[0148] Embodiment 15

[0149] 15.1 Dissolve 28.5 g of the disalicylic aldehyde compound prepared in Example 5 in 350 mL of tetrahydrofuran, mix with 1.48 g of 1,3-propylenediamine, stir and heat to 50°C. After 24 hours, remove the tetrahydrofuran by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter and dry to obtain 27.1 g of polymeric Schiff base.

[0150] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 20500 g / mol.

[0151] 15.2 Dissolve 14.5 g of the polymeric Schiff base prepared in 15.1 above in 200 mL of tetrahydrofuran, mix with 1.77 g of cobalt acetate in 30 mL of methanol solution, heat to 60°C, and after 36 hours, remove the tetrahydrofuran and methanol under vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 13.8 g of a polymeric Schiff base cobalt catalyst.

[0152] 15.3 The reaction flask was repeatedly evacuated and filled with nitrogen, and 232 g of glycolide, 0.25 g of benzyl alcohol, 1.3 g of tert-butyl glycidyl ether, and 3.1 g of the Schiff base cobalt catalyst prepared in 15.2 were added into the reaction flask in sequence. The mixture was stirred and the temperature was rapidly raised to 160°C. After 18 h, 222.7 g of polyglycolic acid was obtained with a yield of 96%.

[0153] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 76000 g / mol.

[0154] Example 16

[0155] 16.1 Dissolve 28.2 g of the disalicylic aldehyde compound prepared in Example 5 in 300 mL of tetrahydrofuran, mix with 3.54 g of 4,5-dichloro-o-phenylenediamine, stir and heat to 45°C. After 30 h, remove the tetrahydrofuran by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 100 mL of ethanol for washing, filter and dry to obtain 28.7 g of polymeric Schiff base.

[0156] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 25000 g / mol.

[0157] 16.2 Dissolve 15.5 g of the polymeric Schiff base prepared in 16.1 above in 250 mL of toluene, mix with 20 mL of toluene solution of 1.62 g of ethoxyaluminum, heat to 90°C, and after 24 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol, wash, filter, and dry to obtain 15 g of a polymeric Schiff base aluminum catalyst.

[0158] 16.3 The reaction bottle was repeatedly evacuated and filled with nitrogen, and 232 g of glycolide, 0.2 g of benzyl alcohol and 3.2 g of the above-mentioned Schiff base aluminum catalyst were added into the reaction bottle in sequence. After mixing and stirring, the temperature was rapidly raised to 155°C. After 20 hours, 222.0 g of polyglycolic acid was obtained with a yield of 95.7%.

[0159] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 96000 g / mol.

[0160] Embodiment 17

[0161] 17.1 Dissolve 28 g of the disalicylic aldehyde compound prepared in Example 5 in 250 mL of toluene, mix with 2.44 g of 4-methyl-o-phenylenediamine, stir and heat to 40°C. After 36 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 150 mL of ethanol for washing, filter and dry to obtain 27.4 g of polymeric Schiff base.

[0162] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 28300 g / mol.

[0163] 17.2 Dissolve 15 g of the polymeric Schiff base prepared in 17.1 above in 300 mL of tetrahydrofuran, mix with 1.9 g of stannous chloride in 50 mL of ethanol solution, heat to 65°C, and after 48 hours, remove the tetrahydrofuran and ethanol under vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 14.8 g of a polymeric Schiff base tin catalyst.

[0164] 17.3 The reaction bottle was repeatedly evacuated and filled with nitrogen, and 232 g of glycolide, 0.22 g of benzyl alcohol and 3.23 g of the above-mentioned Schiff base tin catalyst were added into the reaction bottle in sequence. After mixing and stirring, the temperature was rapidly raised to 150°C. After 24 hours, 221.3 g of polyglycolic acid was obtained with a yield of 95.4%.

[0165] The polyglycolic acid obtained in this example was analyzed by gel permeation chromatography, and the number average molecular weight of the polyglycolic acid was measured to be 88000 g / mol.

[0166] Comparative Example 1

[0167] 1.1 Dissolve 0.42 g of 2,4-diacetylphloroglucinol in 100 mL of toluene, mix with 0.22 g of 4-methyl-o-phenylenediamine, stir and heat to 40°C. After 36 hours, remove the toluene by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 150 mL of ethanol for washing, filter and dry to obtain 0.59 g of polymeric Schiff base.

[0168] The obtained polymeric Schiff base was analyzed by gel permeation chromatography, and the number average molecular weight of the polymeric Schiff base was measured to be 7600 g / mol.

[0169] 1.2 Dissolve 0.33 g of the polymeric Schiff base prepared in 1.1 above in 100 mL of tetrahydrofuran, mix with 0.2 g of stannous chloride in 30 mL of ethanol solution, heat to 65°C, and after 48 hours, remove the tetrahydrofuran and ethanol by vacuum at a vacuum degree of 300 Pa. When no more liquid is distilled out, add 50 mL of ethanol for washing, filter, and dry to obtain 0.43 g of a polymeric Schiff base tin catalyst.

[0170] 1.3 The reaction bottle was repeatedly evacuated and filled with nitrogen, and 23.2 g of glycolide, 0.022 g of benzyl alcohol, and 0.32 g of the above-mentioned Schiff base tin catalyst were added to the reaction bottle in sequence. After mixing and stirring, the temperature was quickly raised to 150°C. After 24 hours, 21.8 g of polyglycolic acid was obtained with a yield of 94.1%.

[0171] The polyglycolic acid obtained in this example was subjected to gel permeation chromatography analysis, and the number average molecular weight of the polyglycolic acid was measured to be 67000 g / mol. Compared with Example 17, the molecular weight and yield were both reduced.

[0172] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A polymeric Schiff alkali metal compound having a structure shown in Formula I to Formula IV: in, R1 is selected from substituted or unsubstituted alkyl, cycloalkyl, aryl or heteroaryl; R2 is selected from the group remaining after removing two hydroxyl groups from polyether diol; R3 is selected from hydrogen, halogen, nitro, substituted or unsubstituted alkyl or alkoxy; R4 is selected from halogen, substituted or unsubstituted alkoxy or ester; M1 is selected from zinc, cobalt, nickel or tin; M2 is selected from aluminum, indium, chromium, iron, manganese, cerium or yttrium; n is the degree of polymerization.

2. The polymeric Schiff alkali metal compound according to claim 1, characterized in that The R1 is selected from substituted or unsubstituted C2-C6 alkyl, C3-C12 cycloalkyl, C6-C12 aryl or C4-C11 heteroaryl; The R2 is selected from the group remaining after removing two hydroxyl groups from the polyether diol; The R3 is selected from hydrogen, halogen, nitro, substituted or unsubstituted C1-C6 alkyl or C1-C6 alkoxy; The R4 is selected from halogen, substituted or unsubstituted C1-C6 alkoxy or ester; n is any integer from 5 to 100.

3. The polymeric Schiff alkali metal compound according to claim 2, characterized in that The R1 is selected from substituted or unsubstituted C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, phenyl; The R2 is selected from the group remaining after removing two hydroxyl groups from the polyether diol; The R3 is selected from hydrogen, halogen, nitro, substituted or unsubstituted methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, methoxy, ethoxy, n-propoxy, isopropoxy; The R4 is selected from halogen, substituted or unsubstituted methoxy, ethoxy, n-propoxy, isopropoxy, carbomethoxy or carboethoxy.

4. The polymeric Schiff alkali metal compound according to claim 3, characterized in that The R1 is selected from ethylenediamine, 1,3-propylenediamine, 1,2-propylenediamine, 2-methyl-1,3-propylenediamine, 2,2'-dimethylpropylenediamine, 1,4-butylenediamine, 1,2-cyclohexyldiamine, o-phenylenediamine, 3-nitro o-phenylenediamine, 4-nitro o-phenylenediamine, 3-bromo o-phenylenediamine, 4-bromo o-phenylenediamine, 4,5-dibromo o-phenylenediamine, 4-bromo-5-fluoro o-phenylenediamine, 4-bromo-5-methyl o-phenylenediamine, 4-chloro-5-bromo o-phenylenediamine, 3-methyl-5-bromo o-phenylenediamine, 4-methoxy o-phenylenediamine, The group remaining after removing two amino groups from diamine, 4-chloro-5-fluoro-o-phenylenediamine, 4,5-dichloro-o-phenylenediamine, 4-chloro-o-phenylenediamine, 4-trifluoromethyl-o-phenylenediamine, 3-chloro-o-phenylenediamine, 3-chloro-5-trifluoromethyl-o-phenylenediamine, 4,5-difluoro-o-phenylenediamine, 4-fluoro-o-phenylenediamine, 3-fluoro-o-phenylenediamine, 3,4-difluoro-o-phenylenediamine, 3,5-difluoro-o-phenylenediamine, 4,5-dimethyl-o-phenylenediamine, 4-methyl-o-phenylenediamine, 3,5-dimethyl-o-phenylenediamine or 4-chloro-5-methyl-o-phenylenediamine; The R2 is selected from the group remaining after removing two hydroxyl groups from polyethylene glycol, polypropylene glycol or polytetrahydrofuran; R3 is selected from hydrogen, -CH3, -CH2CH3, -CH(CH3)2, -OCH(CH3)2, -C(CH3)3, -OCH3 or -OCH2CH3; The R4 is selected from -OCH3, -OCH2CH3, -OCH(CH3)2, -Cl or -OOCCH3.

5. The method for preparing the polymeric Schiff alkali metal compound according to any one of claims 1 to 4, comprising the following steps: a) reacting a polyether glycol with an alkali metal to obtain a polyether glycol alkali metal salt; b) reacting a polyether glycol alkali metal salt with chloromethyl salicylaldehyde to obtain a polyether glycol disalicylicylaldehyde compound; c) reacting a polyether diol disalicylic aldehyde compound with a diamino compound to obtain a Schiff base polymer; d) reacting the Schiff base polymer with a metal compound to obtain a polymeric Schiff base metal compound.

6. The preparation method according to claim 5, characterized in that: The synthesis of the chloromethyl salicylaldehyde comprises the following steps: The salicylaldehyde compound and the formaldehyde compound are reacted with a catalyst to generate chloromethyl salicylaldehyde; The salicylaldehyde compound includes at least one of salicylaldehyde, 3-methyl salicylaldehyde, 3-methoxy salicylaldehyde, 3-ethoxy salicylaldehyde, 3-tert-butyl salicylaldehyde, 3-bromo salicylaldehyde, 3-chloro salicylaldehyde, 5-chloro salicylaldehyde, 5-methyl salicylaldehyde and 5-nitrosalicylicylaldehyde; The formaldehyde compound includes at least one of formaldehyde, trioxymethylene or polyformaldehyde; The molar ratio of the salicylaldehyde compound to the formaldehyde compound is 1:1 to 1:2; The reaction temperature is 0 to 95°C, and the reaction time is 2 to 60 hours; The catalyst is at least one of HCl, concentrated sulfuric acid, phosphoric acid, acetic acid, aluminum chloride, zinc chloride, and tin chloride.

7. The preparation method according to claim 5, characterized in that: The reaction temperature of the polyether diol and the alkali metal is 25 to 100° C., and the reaction time is 1 to 10 hours; The molar ratio of the polyether diol to the alkali metal is 1:2.1 to 1:4; The alkali metal includes one of lithium, sodium and potassium; In the step b), the molar ratio of the chloromethyl salicylaldehyde to the polyether glycol alkali metal salt is 2:1 to 3:1; the reaction temperature is 20 to 120° C., and the reaction time is 2 to 48 hours; In the step c), the molar ratio of the polyether diol disalicylic aldehyde compound to the diamino compound is 1:0.6-1.5; the reaction temperature is 20-100° C., and the reaction time is 2-48 hours; In the step d), the metal compound includes at least one of zinc chloride, zinc acetate, ethyl zinc, stannous chloride, ferric chloride, indium chloride, cobalt acetate, aluminum isopropoxide, aluminum ethoxide, nickel acetate and triethylaluminum; the molar ratio of the diamino compound residue in the Schiff base polymer to the metal compound is 1:1 to 1:1.2; the reaction temperature is 20 to 120° C., and the reaction time is 2 to 100 hours.

8. Use of the polymeric Schiff alkali metal compound according to any one of claims 1 to 4 or the polymeric Schiff alkali metal compound prepared by the preparation method according to any one of claims 5 to 7 as a catalyst in the preparation of cyclic ester polymers.

9. A method for preparing polyglycolic acid, comprising the following steps: In an inert atmosphere, glycolide or a mixture of glycolide and an epoxy compound is reacted in the presence of a catalyst and an initiator to obtain polyglycolic acid; The catalyst is the above-mentioned polymeric Schiff alkali metal compound or the polymeric Schiff alkali metal compound prepared by the above-mentioned preparation method.

10. The preparation method according to claim 9, characterized in that: The ratio of the mass of the catalyst to the mass of the glycolide is 1:(20-2000); The reaction temperature is 120-240° C., and the reaction time is 2-24 hours.

Citation Information

Patent Citations

  • Bimetallic Schiff base coordination metal compound and preparation method thereof

    CN113248698A

  • Eight-center Schiff base metal catalyst, preparation method thereof and preparation method of polyglycolic acid

    CN118085254A

  • Five-center Schiff base metal catalyst, preparation method thereof and preparation method of polyglycolic acid

    CN118085256A

  • Method of Preparing Poly(Alkylene Carbonate) via Copolymerization of Carbon Dioxide / Epoxide in the Presence of Novel Complex

    US20160304664A1

Cited By

  • Method for preparing polyglycolide under catalysis of metal-based ionic liquid

    CN121086205A